An efficient methodology to generate optimal inputs for the preliminary design of centrifugal compressor impellers. (August 2020) - Bourabia, Lakhdar; Khalfallah, Smail; Cerdoun, Mahfoudh; Chettibi, Taha
Preliminary design of centrifugal compressors is an emphasized step, which initiates the design process. Even with the use of quick analysis methods such as one-dimensional models, preliminary design still occupies a substantial part of the total design time. Among the factors that can lengthen this time or even cause the design failure is the inappropriate selection of the design input parameters. The present paper proposes a methodology to generate optimal inputs for the preliminary design, which reduces the design time and optimizes its overall performance. This is achieved, firstly, by performing an aerothermodynamic analysis that defines the appropriate input parameters, which will be used by a preliminary design code. This analysis has allowed identifying three pilot parameters (inlet relative Mach number, work input factor, and slip factor) to guide the generation of adequate input parameters. This input parameter generator, which reduces considerably the failure rate, is then exploited efficiently in an optimization process considering the pilot parameters as decision variables. Therefore, the proposed input parameter generator is coupled with a preliminary design code and an optimization algorithm. The proposed input parameter generator was validated on four existing compressors, showing a gain of more than 90% of the design time. Mainly, the proposed optimization has created a preliminary design trade-off having the target requirements and with optimized off-design performance.